Herbal treatment of secretory diarrhea - H.M. Asif; Khan Usmanghni; Muhammad Akram; Naveed Akhtar; Qaiser Jabeen; S.M. Ali Shah; Riazur Rehman; Khalil Ahmed; Tariq Saeed (International Journal of Phytomedicine, 2010)
The research study is conducted to understand interaction of illness, symptoms, context, patients response and the clinical skill vis a vis better management of secretory diarrhea. Specific aim of this study is to determine the impact of intensive medical intervention with herbal drug “Dirasif” (Test) and allopathic drug “Furoxone” (Control) to treat secretory diarrhea. This is randomized controlled clinical trial in primary care with an open intervention. All patients judged by the physician to need either herbal or allopathic medicine for secretory diarrhea are randomized in treatment therapy. Clinical trial was conducted on hundred patients from both groups i.e.50 patient from control and 50 from experimental group having age between 12-40 year. Comparison of data recorded by participants relating to these variables showed significant differences between test and control groups (p < 0.05) despite the fact that no side effects were recorded in test group. Overall clinical success was observed in both treatment groups however the efficacy of the test treated medication (Dirasif) was superior as p=0.03. Dirasif is more effective than the Furoxone in the treatment of secretory diarrhea in Gadap community Karachi, Pakistan.